The Relationship Between Permissive Parenting Style and Bullying Behavior Among Nursing Students - Aziz, Shovi Nur; Abdillah, Hadi; Martini, Eva (Jurnal Keperawatan Priority, 2025)
This study aimed to examine the relationship between permissive parenting style and bullying behavior among undergraduate nursing students at Muhammadiyah University of Sukabumi. University students experience significant social and psychosocial development, and inadequate internalization of parental values can lead to maladaptive behaviors such as bullying. This research employed a quantitative cross-sectional design with purposive sampling. Data were collected using validated questionnaires on parenting style and bullying behavior and analyzed using the Chi-Square test. The results showed a significant relationship between permissive parenting style and bullying behavior (p=0.000, p<0.05). Students raised with a permissive parenting style were more likely to exhibit moderate levels of bullying behavior. These findings suggest that permissive parenting, which grants children excessive freedom with minimal supervision, can increase the likelihood of aggressive behaviors such as bullying. Efforts to strengthen parental involvement and guidance are essential to prevent bullying among university students.